The Effect Of Progressive Muscle Relaxation On Insomnia Among The Elderly: A Literature Review - Apriany, Anita; Aljaberi, Musheer Abdulwahid (International Journal of Health Sciences, 2023)
Introduction: The term "elderly" refers to a stage of human existence characterized by a decline in the body's capacity to respond to external stress and a failure to maintain body equilibrium in physiological stress situations. Patients who are elderly are more likely to suffer from sleep difficulties, including insomnia, which is one of the effects they experience. Insomnia is a sleep disorder defined by a lack of capacity to establish or sustain regular sleep schedules; symptoms usually appear within a week. Material and Methods: This research is a review of the existing literature. The topic, articles from 2018 to 2023, were chosen from various online databases, including Science Direct, PubMed, and Google Scholar. The PRISMA approach was utilized by analyzing the literature review. Results: After sifting through 315 publications, only 16 studies were deemed suitable for analysis. The conclusion drawn from these studies is that PMT significantly decreases the prevalence of insomnia in the elderly. Conclusion: Progressive Muscle Relaxation has been shown in various studies to alleviate insomnia in the elderly.